Review of management priorities for invasive infections in people who inject drugs: highlighting the need for patient‐centred multidisciplinary care. Issue 2 (26th June 2022) - Attwood, Lucy O; McKechnie, Megan; Vujovic, Olga; Higgs, Peter; Lloyd‐Jones, Martyn; Doyle, Joseph S; Stewardson, Andrew J
Summary: There has been a global increase in the burden of invasive infections in people who inject drugs (PWID). It is essential that patient‐centred multidisciplinary care is provided in the management of these infections to engage PWID in care and deliver evidence‐based management and preventive strategies. The multidisciplinary team should include infectious diseases, addictions medicine (inclusive of alcohol and other drug services), surgery, psychiatry, pain specialists, pharmacy, nursing staff, social work and peer support workers (where available) to help address the comorbid conditions that may have contributed to the patient's presentation. PWID have a range of antimicrobial delivery options that can be tailored in a patient‐centred manner and thus are not limited to prolonged hospital admissions to receive intravenous antimicrobials for invasive infections. These options include discharge with outpatient parenteral antimicrobial therapy, long‐acting lipoglycopeptides (dalbavancin and oritavancin) and early oral antimicrobials. Open and respectful discussion with PWID including around harm reduction strategies may decrease the risk of repeat presentations with injecting‐related harms.